1988
DOI: 10.1111/j.1365-2125.1988.tb03360.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dose on the glucuronidation and sulphation kinetics of diflunisal in man: single dose studies.

Abstract: 1 The effect of dose (100 mg, 250 mg, 500 mg, 750 mg and 1000 mg) on the glucuronidation and sulphation of diflunisal was studied in six healthy volunteers. 2 Total urinary recovery ranged from 78.9 ± 11.9% to 91.5 ± 18.7% of the administered dose. Urinary recovery (normalized for total urinary recovery) of diflunisal sulphate (DS) significantly increased with dose from 9.3 ± 3.7% to 18.1 ± 4.8%.3 Normalized urinary recovery for diflunisal phenolic glucuronide (DPG) was unaffected by dose (range: 30.6 ± 3.8% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
(22 reference statements)
2
18
1
Order By: Relevance
“…Meffin et al (1983) studied the multiple dose pharmacokinetics of diflunisal in patients with osteoarthritis. They found that the dose-dependent reduction in the oral clearance (Loewen et al, 1988), which is in contrast to the results obtained by Meffin et al (1983). Since steady state plasma concentrations of diflunisal following daily doses of 1000 mg fall within the.…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…Meffin et al (1983) studied the multiple dose pharmacokinetics of diflunisal in patients with osteoarthritis. They found that the dose-dependent reduction in the oral clearance (Loewen et al, 1988), which is in contrast to the results obtained by Meffin et al (1983). Since steady state plasma concentrations of diflunisal following daily doses of 1000 mg fall within the.…”
Section: Discussioncontrasting
confidence: 54%
“…In single-dose studies we found no evidence of saturation of the sulphation of diflunisal (Loewen et al, 1988). The present results show that even after multiple dosing, sulphation of diflunisal is not saturated and thus follows linear kinetics.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations